Token-based Single Sign-on with JWT as Information System Dashboard for Government - I Putu Arie Pratama; Linawati Linawati; Nyoman Putra Sastra (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2018)
Various web-based information systems are developed by Indonesian government to improve quality of services for their society. It encourages users, generally civil servants, to perform different authentications on used information systems and have to remember credentials. Account management of the users poses another challenge for administrators. Single Sign-On (SSO) can be the solution by providing a service of centralized authentication and user account management. This study applies a token-based SSO architecture and uses Json Web Token (JWT) to grant permission authorities, since JWT can provide a claim process between 2 parties. Additionally, the built-in dashboard lists associated information systems to facilitate accessing for the authenticated users. This study will discuss JWT implementation on the dashboard of government information systems that implements SSO, which will generate the permission authorities securely for connected information systems on SSO.